THE RELATIONSHIP BETWEEN SAFETY BEHAVIOUR AND SAFETY AWARENESS TOWARDS COMMUTING ACCIDENT AMONG EMPLOYEES IN ONE OF GOVENRMENT-LINKED COMPANIES (Social Security Management Journal, 2024)
Road safety has been raised as a critical problem among Malaysian employees. Safety awareness had influenced employee safety behaviour directly and indirectly. This study aimed to access the relationship between safety behaviour and safety awareness towards commuting accidents among one of Government link Companies’ (GLC) employees. The hypothesis for this study were developed based on research questions and objectives to express the relationship between safety behaviour (safety participation and safety compliance) and safety awareness (safety knowledge and safety motivation). A self-administrative questionnaire was used for data collection which involved 160 employees from one of the GLCs in Kuala Lumpur. Data collected were analysed using Statistical Package for the Social Science (SPSS) Version 25.0 specifically for descriptive and inferential analysis. The regression analysis revealed that safety participation has a positive significant relationship towards safety knowledge and safety motivation. Thus, it is important to conduct more campaigns and awareness programmes to cultivate road safety among employees. Employees also should be given training related to road safety to reduce commuting accident. Comprehensively, this study may provide guidance on enforcement of strict traffic rules and procedures to reduce accident rates in Malaysia.